Planeación y seguimiento de caminos a través de algoritmos genéticos para el problema de agente viajero con múltiples agentes robots móviles en escenarios dinámicos (2016)
This project consists of designing and implementing a solution for the Multiple Travel Salesman Problem (MTSP) in the case of multiple mobile robots in dynamic scenarios. One of the main challenges faced in this work is that MTSP is a NP-complete problem. This kind of problem is characterized by being highly studied in computer science because it is not known whether it has an efficient solution (in polynomial time) or not. Therefore, this project investigates and implements techniques of genetic algorithms in order to solve the theoretical problem efficiently. Once a theoretical solution is found, it is necessary to understand the physical scenario in which the mobile robots will be deployed. For this reason, we implemented path planning and tracking algorithms on a physical stage in order for generating routes that robots must navigate. Furthermore, the previous operation is complemented by the implementation of obstacle's avoidance algorithms for the management of dynamic scenarios, in which unexpected obstacles may exist and they were not contemplated in the initial planning. Finally, tests are performed in the simulation and laboratory level to measure the quality of the proposed solution.--Tomado del Formato de Documento de Grado.